[4]Cyclofluorene: Unexpected Influence of Alkyl Chain Length. Issue 9 (14th September 2018) - Sicard, Lambert; Jeannin, Olivier; Rault‐Berthelot, Joëlle; Quinton, Cassandre; Poriel, Cyril
Abstract: Presented here is the study of a new example of [4]cyclofluorene, with ethyl chains on the bridgeheads. Its molecular structure was established by solution NMR spectroscopy and single‐crystal X‐ray diffraction. Three successive oxidation processes and one reversible reduction were observed through cyclic voltammetry. The optical properties were characterized both in solution and thin film by UV/visible spectroscopy as well as stationary and time‐resolved fluorescence. It was found that this [4]cyclofluorene displays different characteristics compared with the other [4]cyclofluorenes substituted by methyl or propyl chains: a simple modification of the chain length induces a non‐negligible effect on the emission properties, which must be linked to the specific arrangement of the fluorene units. Furthermore, single‐crystal X‐ray diffraction reveals the formation of a pseudo‐tubular solid‐state arrangement of fully symmetrical ring structures, which was not observed for the other members of the [4]cyclofluorenes family. This finding could open the way to modulation of properties of cyclofluorenes through alkyl chain engineering. Abstract : Going in circles : Reported is the unforeseen effect of chain length modification (substitution of the bridgehead positions with ethyl chains) on the structural and emission properties of a new example of cyclic tetrafluorene, namely the [4]cyclo‐9, 9‐diethyl‐2, 7‐fluorene (see figure).